Pengelolaan Limbah Medis Padat Diwilayah Kerja Puskesmas Pangkalan Kasai Kecamatan Seberida Kabupaten Indragiri Hulu Tahun 2020 - Desty Andria Lista andrialista; Nila Puspita Sari; Hastuti Marlina (Jurnal Kesehatan Komunitas, 2021)
Medical waste is the result of the activities of a hospital,clinic. The purpose of this research in figuring out how the management medical waste which in done in every puskesmas. This research is qualitative research descriptive research design, Data collection by conductor health service unit that is dangerous and can cause health probelms for the community, patients, visitors and officers who contribute to control in the community health center.ing in-depth interviews and observations with the leader puskesmas, environmenral health, nourse,clenaing service. The study was conducted in july 2020 at the Puskesmas Pangkalan Kasai Kecamatan Seberida Kabupaten Indragiri Hulu. Research’s outcome has showed that system management of medical waste has not been standart yet, that one is happaned caused by the limitation of infrastructure as well as there is no keman’rule in every Puskesmas that should banish their own medical waste. Then this research’s outcomethat has been done by the researcher givean advice to Puskesmas Pangkalan Kasai to carry out the banishing their own medical waste to a health service having a incinerator.